Proximal Hypospadias - Kate H. Kraft; Aseem R. Shukla; Douglas A. Canning (The Scientific World Journal)
Hypospadias results from abnormal development of the penis that leaves the urethral meatus proximal to its normal glanular position. Meatal position may be located anywhere along the penile shaft, but more severe forms of hypospadias may have a urethral meatus located at the scrotum or perineum. The spectrum of abnormalities may also include ventral curvature of the penis, a dorsally redundant prepuce, and atrophic corpus spongiosum. Due to the severity of these abnormalities, proximal hypospadias often requires more extensive reconstruction in order to achieve an anatomically and functionally successful result. We review the spectrum of proximal hypospadias etiology, presentation, correction, and possible associated complications.